Bullying in prisons in Argentina: a study of personality, mental health and attitudes - Resett, Santiago (The journal of forensic psychiatry & psychology, 2022)
Bullying in prisons is a construct with important psychosocial and physical consequences. The research examines the nature and extent of bullying in four prisons in Argentina, exploring demographics, personality, mental health, and attitudes towards bullying. Seven hundred and eighteen adult prisoners took part (667 men, 48 women, and 3 transgender), completing the DIPC-SCALED-r version (Direct and Indirect Prisoner Behaviour Checklist), and measures of personality, mental health, and bullying attitudes. Dark Triad traits, attitudes supportive of prison bullying/disapproving of victims, and prison experience were considered likely to predict perpetration, with depression predicting victimisation. Results demonstrated that bullying was predicted by higher levels of Dark Triad personality, specific attitudes supportive of bullying, younger age, and certain offence types (i.e. homicide/attempted homicide and robbery). Prison experience was not a predictor. Victimisation was a significant predictor of depression. Implications of these findings are outlined, with suggestions for future research made, including proposals for a reformulation of the MMBSS (Multifactor Model of Bullying in Secure Services).